Bibelteologi som skrift? - Berge, Kåre (Dansk Teologisk Tidsskrift, 2009)
This article reviews two books of N. P. Lemche (also published in USA). Lemche discusses how to make biblical theology “after the collapse of history” in the sense of the Copenhagen school. Biblical theology should be based on the texts and narratives not on history. This does not, however, mean a return to literary criticism or structuralism. Biblical texts, in Lemche’s view, should be regarded as arbitrary cultural artifacts, which have to be studied as cultural representations of social conditions in the pre-Christian centuries.